Pengaruh Terapi Bermain Rubik pada Anak Usia Sekolah dalam meningkatkan keterampilan motorik halus - Kurniawan, Ade; Enita, Enita; Gina, Gina; Nuranjani, Tini; Shabrina, Shabrina; Bela, Bela; Firmansyah, Andan (Yayasan Inspirasi El Burhani, 2024)
Abstract Introduction: Playing is a reflection of physical, intellectual, emotional, social abilities and playing is a good medium for learning because by playing, children will speak, learn to adapt to the environment, do what they can, and recognize time, distance and sound.Objective: To apply the Rubik's game to improve fine motor skills in school-aged childrenMethod: This therapy research for playing Rubik's uses the educational method of inviting children to play with Rubik's and forming Rubik's in various shapes. This play therapy was carried out on 9 students at SDN 1 Panaragan, Ciamis District, Ciamis Regency with a total of 30 children as respondents and accompanied by a homeroom teacher. This play therapy is carried out in 2 stages, namely 1) asking children to match the colors on the rubik, 2) asking children to form with patience and continuing to practice, 3) evaluation. Result: The application of play therapy education to students at SDN 1 Panaragan Ciamis gave significant results as proven by 30 respondents. This type of game is challenging and can help develop creativity, problem solving and fine motor skills. This game is very popular throughout the world and is used as an aid in mathematics and art education.Conclussion: After reviewing various theoretical sources regarding the fine motor skills of early childhood, it can be seen how important it is to develop children's fine motor skills as early as possible because motor development is closely related to the development of the motor center in the brain. One way to develop fine motor skills in early childhood is by playing. In the research, the play activities used were playing with rubik's in various shapes, such as forming animals or balls, which can attract children's attention.